Chemopreventive Effect of an In Vitro Digested and Fermented Plant Sterol-Enriched Wholemeal Rye Bread in Colon Cancer Cells - Diego Miedes; Antonio Cilla; Amparo Alegría (Foods, 2023)
Diet is crucial for the prevention of colorectal cancer. Whole grains are the source of beneficial compounds for this, such as fiber. The enrichment of wholemeal rye bread with plant sterols (PSs) could increase its beneficial effects. This study aimed to assess the potential antiproliferative effect of this enriched food on colon adenocarcinoma cells (Caco-2) compared with a non-enriched one. After a human oral chewing, simulated semi-dynamic gastrointestinal digestion and colonic fermentation in a simgi® system, fermentation liquids (FLs) obtained were used as treatment for cells. Cytotoxicity assay showed that samples diluted 1/5 (v/v) with DMEM are not toxic for non-tumoral cells, whereas they damage tumoral cells. Samples with PS (FLPS) produced a higher chemopreventive effect (vs. blank) in MTT and apoptosis assays, as well as higher gene expression of TP53 and Casp8. Nevertheless, FL0 (without PS) produced a higher chemopreventive effect in a cell cycle and reduced glutathione and calcium assays, besides producing higher gene expression of Casp3 and lower CCND1. The distinct antiproliferative effect of both FLs is attributed to differences in PSs, short chain fatty acids (lower concentration in FLPS vs. FL0) and antioxidant compounds. These results may support wholemeal rye bread consumption as a way of reducing the risk of colorectal cancer development, although further research would be needed.